Effects of 90% oxygen exposure on the ultrastructure of the tracheal epithelium in rabbits - Konrádová, V; Janota, J; Sulová, J; Suková, B; Copová, M (Respiration; international review of thoracic diseases, 1988)
Numerous signs of pathological alteration were induced in the pseudostratified ciliated epithelium by a 2-hour exposure to 90% oxygen. The ciliary border injury was especially conspicuous, the mean number of cilia in a given area was significantly (p less than 0.005) reduced and morphological signs of impaired self-cleaning ability were revealed. Ciliated cells were severely injured showing apical blebbing and swelling of cell organelles. The reaction of goblet cells to exposure to O2 was rapid discharge of mucus, but the mechanism of mucus evacuation was not substantially influenced. At the ultrastructural level, only a mild effect of humidification of the oxygen was observed.
Keywords: Animals; epitel; Rabbits; Female; Humidity; Cilia; ženské pohlaví; cilie; Trachea; vlhkost; časové faktory; Time Factors; trachea; Epithelium; Male; Oxygen; králíci; zvířata; mužské pohlaví; kyslík